"I Hope to Remain the Same": Continuity and Change in College Students' Sexual Possible Selves across the First Semester. Issue 1 (2nd January 2019) - Anders, Kristin M.; Olmstead, Spencer B.
Abstract: This study replicates and extends research on college students' sexual possible selves by longitudinally examining their sexual expectations, fears, and behavioral strategies at the beginning and end of the first semester in college. Open-ended responses were collected at two time points (T1, N = 78; T2, N = 40) and were analyzed using directed content analysis. First semester students' salient expectations and fears focused on abstinence, interpersonal relationships, quantity, conditional sex, decreasing/avoidant behaviors, and fears related to sexual health/well-being, sexual assault/coercion, self-focus, and increased sexual risk at both T1 and T2. However, two new themes emerged at T2: maintain (expected) and partner-focus (feared). At both time points, behavioral strategies included abstinence, making opportunities, restricting boundaries, sexual health/well-being, thoughtful/informed decisions, and self-assertion/protection . Quantitative frequency comparisons were also conducted to examine changes in the prevalence of the reported categories and indicated shifts in salient expectations, fears, and strategies across the first semester. Implications for sexual education are discussed.